High-intensity interval walking training using internet of things (IoT): past and future - Hiroshi Nose; Mayuko Morikawa; Mayuka Furihata; Shizue Masuki (Japanese Society of Physical Fitness and Sports Medicine, 2021)
Facing the rapid growth in the elderly population worldwide, the need for exercise prescriptions according to individual physical fitness has become increasingly apparent. Despite this, the training system broadly available has not been developed. Accordingly, we have developed a system with internet of things (IoT) for middle-aged and older people called "e-Health Promotion System", based on interval walking training (IWT). IWT is a training regimen repeating 5 sets of fast walking at more than 70% peak aerobic capacity (VO2peak) and slow walking at ~40% VO2peak for 3 min each per day. The system is composed of a device that is equipped with a tri-axial accelerometer and a barometer, and connected to a central server. The sever has a program for storing walking records transferred from the device through the internet, as well as for instructing participants regarding IWT in a feedback manner based on the server database. Using this system, we examined the effects of 5-month IWT in more than 8,700 middle-aged and older people, and found that the training increased VO2peak by 15%, improved lifestyle-related disease symptoms by 20%, and reduced healthcare costs by ~20% on average. We subsequently reported that the effects of IWT depended only on average fast walking time, rather than average slow or total walking time per week. Recently, we also developed a mobile application program to provide participants with this service on their smartphone so that we can examine the effects of IWT in a much larger population of people at the same time and across generations. The system has great potential to increase interdisciplinary studies between sports sciences and other fields of science to establish and promote a society for health and longevity.